The Phenomenal-Intentional Nature of Happiness: A contemporary Approach to Epictetus and Stoicism - González Estrada, Allan Arturo (2019)
The present paper offers a contrast between the philosophical ideas of Stoicism and contemporary ideas in philosophy of the mind, to understand the nature of intentionality and phenomenal experience as a fundamental element in a theory of "happiness". The metaphysical foundation that I fallow is based on a physicalist approach in non-reductive terms, from a perspective derived from a phenomenal-intentionality program, that is, the idea that intentionality depends on its phenomenal characteristics, in this way, an analysis of popular psychology and propositional attitudes as a contemporary basis for reinterpreting metaphysics and stoic epistemology in particular from the ideas exposed by Epictetus is possible. It is concluded that an interpretation more in line with the phenomenal characteristics of intentionality can provide a solid base to understand the nature of representation and the change in the narrative suggested by Epictetus rather than the representational theories such as those advocated by Michael Tye as the path to understand happiness. Keywords: Happiness, Intentionality, Phenomenal Character of Experience, Stoicism, Epictetus.